Vagal Nerve Stimulation in the Treatment of Drug-Resistant Epileptic Encephalopathies in Inborn Errors of Metabolism: Report of 2 Cases. Issue 4 (22nd October 2015) - Grioni, Daniele; Landi, Andrea; Gasperini, Serena; Trezza, Andrea; Fiori, Leonardo; Rigoldi, Miriam; Parini, Rossella; Sganzerla, Erik Pietro
Patients affected by inborn errors of metabolism can develop catastrophic epilepsies ineligible for resective surgery. Few reports concerning vagal nerve stimulation in patients with epileptic encephalopathy in the context of metabolic diseases have been published in the literature. Drug-resistant epilepsies in metabolic disease could be a specific target for vagal nerve stimulation, although the efficacy of this technique in these patients still needs to be proved. The authors report our experience in treating refractory epilepsy with vagal nerve stimulation in 2 patients affected by inborn errors of metabolism. The first patient is a 23-year-old patient affected by glutaric aciduria type II, the other one is a 16-month-old child with nonketotic hyperglycinemia. Vagal nerve stimulation reduced seizures up to 50% in the first case and up to 90% in the second one.